Protein targeting by the itaconate family in immunity and inflammation - Day, Emily A; O'Neill, Luke A J (Biochemical journal, 2022)
Immune cells are metabolically plastic and respond to inflammatory stimuli with large shifts in metabolism. Itaconate is one of the most up-regulated metabolites in macrophages in response to the gram negative bacterial product LPS. As such, itaconate has recently been the subject of intense research interest. The artificial derivatives, including 4-Octyl Itaconate (4-OI) and Dimethyl Itaconate (DI) and naturally produced isomers, mesaconate and citraconate, have been tested in relation to itaconate biology with similarities and differences in the biochemistry and immunomodulatory properties of this family of compounds emerging. Both itaconate and 4-OI have been shown to modify cysteines on a range of target proteins, with the modification being linked to a functional change. Targets include KEAP1 (the NRF2 inhibitor), GAPDH, NLRP3, JAK1, and the lysosomal regulator, TFEB. 4-OI and DI are more electrophilic, and are therefore stronger NRF2 activators, and inhibit the production of Type I IFNs, while itaconate inhibits SDH and the dioxygenase, TET2. Additionally, both itaconate and derivates have been shown to be protective across a wide range of mouse models of inflammatory and infectious diseases, through both distinct and overlapping mechanisms. As such, continued research involving the comparison of itaconate and related molecules holds exciting prospects for the study of cysteine modification and pathways for immunomodulation and the potential for new anti-inflammatory therapeutics.